Early activation of object names in visual search. - Meyer, A; Belke, E; Telling, A; Humphreys, G (2007)
In a visual search experiment, participants had to decide whether or not a target object was present in a four-object search array. One of these objects could be a semantically related competitor (e.g., shirt for the target trousers) or a conceptually unrelated object with the same name as the target-for example, bat (baseball) for the target bat (animal). In the control condition, the related competitor was replaced by an unrelated object. The participants' response latencies and eye movements demonstrated that the two types of related competitors had similar effects: Competitors attracted the participants' visual attention and thereby delayed positive and negative decisions. The results imply that semantic and name information associated with the objects becomes rapidly available and affects the allocation of visual attention.